FEMA GRAS assessment of natural flavor complexes: Asafetida oil, garlic oil and onion oil. (March 2023) - Davidsen, Jeanne M.; Cohen, Samuel M.; Eisenbrand, Gerhard; Fukushima, Shoji; Gooderham, Nigel J.; Guengerich, F. Peter; Hecht, Stephen S.; Rietjens, Ivonne M.C.M.; Rosol, Thomas J.; Harman, Christie L.; Ramanan, Danarubini; Taylor, Sean V.
Abstract: The Expert Panel of the Flavor and Extract Manufacturers Association (FEMA) applies its procedure for the safety evaluation of natural flavor complexes (NFCs) to re-evaluate the safety of Asafetida Oil ( Ferula assa-foetida L.) FEMA 2108, Garlic Oil ( Allium sativum L.) FEMA 2503 and Onion Oil ( Allium cepa L.) FEMA 2817 for use as flavoring in food. This safety evaluation is part of a series of evaluations of NFCs for use as flavoring ingredients conducted by the Expert Panel that applies a scientific procedure published in 2005 and updated in 2018. Using a group approach that relies on a complete chemical characterization of the NFC intended for commerce, the constituents of each NFC are organized into well-defined congeneric groups and the estimated intake of each constituent congeneric group is evaluated using the conservative threshold of toxicological concern (TTC) concept. Data on the metabolism, genotoxic potential and toxicology for each constituent congeneric group are reviewed as well as studies on each NFC. Based on the safety evaluation, Asafetida Oil ( Ferula assa-foetida L.), Garlic Oil ( Allium sativum L.) and Onion Oil ( Allium cepa L.) were affirmed as generally recognized as safe (GRASa) under their conditions of intended use as flavor ingredients. Highlights: Safety evaluation of natural flavoring complexes. Evaluation used procedure developed by the FEMA Expert Panel for natural flavor complexes . FEMA GRAS status determined/affirmed for 3 natural flavor complexes .